The Meaning of Criminal Causing in the Iraqi Penal Code - Fadhil Rekib, Prof. Emad; Tariq Ebrahim, Prof. Dr. Nawal (Basra studies journal, 2024)
The term ’’criminal causing’ is one of an old and frequent terms in the texts of penal laws, including the amended Iraqi Penal Code No. 111 of 1969, which is considered one of the most used laws in this contexts. The problem is not in the frequency or frequent use of this term, but rather in the absence of a specific meaning for criminal causing, which negatively affected the decisions of the criminal judiciary with regard to determining the legal adaptation corresponding to the material incident and the extent of the responsibility of the causer for the criminal result. However, we assumed that the criminal causing has a special meaning upon which the determination of its features, elements, and legal provisions depends, and based on this hypothesis, we have decided to research this problem and treatments.